Circulation of SARS-CoV-2 Variants among Children from November 2020 to January 2022 in Trieste (Italy) - Maria Dolci; Lucia Signorini; Carolina Cason; Giuseppina Campisciano; Paolo Kunderfranco; Elena Pariani; Cristina Galli; Vincenzo Petix; Pasquale Ferrante; Serena Delbue; Manola Comar (Microorganisms, 2022)
Introduction: The ongoing coronavirus disease 19 (COVID-19) outbreak involves the pediatric population, but to date, few reports have investigated the circulation of variants among children. Material and Methods: In this retrospective study, non-hospitalized pediatric patients with SARS-CoV-2-positive nasopharyngeal swabs (NPS) were enrolled at the Institute for Maternal and Child Health-IRCCS Burlo Garofolo, Trieste (Italy), from November 2020 to January 2022. SARS-CoV-2 variants were identified by in vitro viral isolation, amplification, automatic sequencing of the receptor binding domain (RBD) of the SARS-CoV-2 spike coding gene, and subsequent next-generation sequencing. The growth curves of the isolated strains were defined in vitro by infecting Vero-E6 cells and quantifying the viral load in the supernatants up to 72 h post-infection by qRT–PCR. The neutralization activity of sera obtained from a COVID-19 vaccinated subject, recovered (2020) patient, vaccinated and recovered (2021) patient, and seronegative subject was assessed by microneutralization assay against the different variants. Results: In total, 32 SARS-CoV-2-positive children, 16 (50%) females, with a median age of 1.4 years (range: 1 day–13 years), were enrolled. The D614G amino acid substitution was detected in all isolated and amplified viral strains. Of the 32 isolates, 4 (12.5%) carried a nonsynonymous nucleotide mutation leading to the N439K (3/4), lineage B.1.258 (∆H69/∆V70), and S477N (1/4) substitution. In 7/32 (21.8%) isolates, amino acid substitutions allowed the identification of a delta variant, lineage B.1.617.2-AY.43, and in 1/32 (3.1%), the Omicron strain (B.1.1.529.BA1) was identified. The growth curves of the B.1, B.1.258 (∆H69/∆V70), B.1.617.2-AY.43, and B.1.1.529.BA1 variants did not show any significant differences. A reduction in the serum neutralizing activity against B.1.258 (∆H69/∆V70) only in a vaccinated subject (1.7-fold difference), against B.1.617.2-AY.43 in a vaccinated subject and in recovered patients (12.7 and ≥2.5-fold differences, respectively), and against B.1.1.529.BA1 variant (57.6- and 1.4-fold differences in vaccinated and in vaccinated and recovered patients) were observed compared to the B.1 variant. Conclusions: SARS-CoV-2 variants carrying the B.1.258 (∆H69/∆V70) and S477N substitutions were reported here in a pediatric population for the first time. Although the growth rates of the isolated strains (B.1.258, B.1.617.2-AY.43, B.1.1.529.BA1) did not differ from the B.1 variant, neutralizing activity of the sera from vaccinated subjects significantly decreased against these variants. Attention should be devoted to the pediatric population to prevent the spread of new SARS-CoV-2 variants in an unvaccinated and predominantly naive population.